DAMPAK POSITIF ILMU SENI KALIGRAFI TERHADAP KESEHATAN MENTAL - Muhammad Alfi Abrar (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
Calligraphy, as an art of writing closely related to culture and religion, is not only a form of artistic expression but also holds significant therapeutic potential. In psychology, calligraphy can be considered an effective form of non-clinical therapy to support mental and emotional well-being. Through the activity of drawing or writing calligraphy, individuals can express their feelings, manage stress, and enhance their psychological well-being. This study uses a literature review method to examine the impact of calligraphy on mental health by analyzing various relevant sources of literature. The analysis shows that calligraphy provides individuals with an opportunity to express feelings and emotions that may be difficult to articulate with words. The creative process in calligraphy helps relieve stress and anxiety, while also increasing self-control and a sense of achievement. Additionally, calligraphy involving hand movements and rhythm can have therapeutic effects similar to meditation, reducing emotional tension and improving mental well-being.